Daya Serap Air Sebagai Acuan untuk Menentukan Volume Air dalam Pembuatan Adonan Roti dari Campuran Tepung Terigu dan Tepung Singkong - Rusdin Rauf; Dwi Sarbini (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2015)
Cassava flour substitution in the dough preparation often result in dough that is not properly hydrated. The purpose of the research was to determine the proper water volume in making dough from wheat flour and cassava flour mixtures. The research was conducted by analyzing amylograph characteristic and water absorption capacity of wheat flour and cassava flour mixtures. The water absorption was used as a reference to determine the volume of water in the dough preparation of mixed flours. Then, the elongation properties of the doughs were measured. Amylograph data indicated that wheat flour displayed a higher temperatur stability than cassava flour. The more portion of cassava flour, the lower its thermal stability. The water absortion of cassava flour was higher than wheat flour. The increasing of water absorbtion, in line with the increasing of cassava flour portion, which gave a linear trend, R= 0.972. Based on the technique of proportional to water absorption in determine the water volume, the biggest tensile strength of dough was revealed by wheat flour:cassava flour 100:0 and 90:10. However, the highest strain displayed by dough of wheat flour:cassava flour 100:0.ABSTRAKSubstitusi tepung singkong dalam pembuatan adonan roti seringkali menghasilkan adonan yang tidak terhidrasi dengan baik. Tujuan dari penelitian ini adalah untuk menentukan volume air yang tepat dalam pembuatan adonan dari campuran tepung terigu dan tepung singkong. Penelitian dilakukan dengan menganalisis sifat amilografi dan daya serap air dari campuran tepung terigu dan tepung singkong. Data daya serap air dijadikan acuan dalam penentuan volume air pada pembuatan adonan dari campuran tepung terigu dan tepung singkong. Kemudian dilakukan analisis elongasi adonan. Hasil amilografi menunjukkan bahwa tepung terigu lebih stabil terhadap panas dibanding tepung singkong. Makin besar porsi penambahan tepung singkong, semakin kecil stabilitas panasnya. Tepung singkong menunjukkan daya serap air yang lebih tinggi dibanding tepung terigu. Peningkatan daya serap air dari campuran tepung, seiring dengan peningkatan porsi tepung singkong, yang memberikan kecenderungan linear, dengan nilai R = 0,972. Berdasarkan teknik proporsional dengan daya serap air dalam menentukan volume air, tensile strength terbesar diberikan oleh adonan dari tepung terigu:tepung singkong 100:0 dan 90:10. Sedangkan strain tertinggi ditunjukkan oleh adonan campuran tepung terigu:tepung singkong 100:0.